Pituduh dalam Bahasa Jawa: Jawanisasi Orang Jawa - Sri Ningsih (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
This paper is the result of the research in the area of the local wisdom of the Javanese society in theform of the Javanese (advice) speech. The contect of the research problem is the understanding ofthe Javanese (advice) speech which is understood as one of the Javanese local wisdoms in the formsof the moral messages in the Javanese society. The research method used in this research is thecombination between linguistic and anthropological methods (ethnolinguistics), specifically usingthe etnosign methodology. The results of this research are in the forms of the classification and thelinguistic expression categorization which can be stated as follows: (1) the conception of theJavanese about personal management, (2) the conception of the Javanese about World and Wordly,(3) the conception of the Javanese about family and society, (4) the conception of the Javaneseabout nations, (5) the concept about spiritual superiority, and (6) the conception of Javanese aboutthe belief/divinity. From the discussion of the Javanese (advice) speech, it needs to conduct thereinterpretation and the revitalization accurately about the ways of the Javanese thought in the pastand in the current society to intergrate the knowledge and cosmology which can be referred tounderstand the cultural problems.